The Application of Problem-Based Learning Models with Peer Tutoring Assistance on Problem-Solving Abilities and Cognitive Learning Outcomes in Science for Junior High School Students - Nabilah; Septiko Aji; Muhammad Ahganiya Naufal; Prasetyo Listiaji (Journal of Environmental and Science Education, 2026)
The implementation of the Merdeka curriculum as an effort to improve the quality of education focuses on 21st-century skills, including critical thinking skills, which are essential for problem-solving. Evidence indicates junior high school students exhibit low problem-solving and cognitive ability. This study aims to analyze the differences and levels of problem-solving ability and cognitive outcomes in science after implementing a Problem-Based Learning model supported by Peer Tutoring. This quasi-experimental research used a non-equivalent control group design at Semarang State Junior High School 8, with cluster random sampling. Data were gathered through observation, test, and documentation. The research results showed a significant improvement in problem-solving ability and cognitive outcomes in science after implementing the Problem-Based Learning (PBL) model with Peer Tutoring. This is evidenced by the results of an independent t-test, which found that tcount was greater than ttable. The average posttest problem-solving score in the experimental class was higher (80.8) than in the control class (70.7). Similarly, the average posttest score for cognitive learning outcomes in science in the experimental class was higher (81.6) than in the control class (74.4). Analysis of problem-solving ability level and cognitive learning outcomes level showed an increase in the number of students in each indicator's good and very good criteria.